2016
DOI: 10.1371/journal.pone.0161705
|View full text |Cite|
|
Sign up to set email alerts
|

Who Lives Where and Does It Matter? Changes in the Health Profiles of Older People Living in Long Term Care and the Community over Two Decades in a High Income Country

Abstract: BackgroundThere have been fundamental shifts in the attitude towards, access to and nature of long term care in high income countries. The proportion and profile of the older population living in such settings varies according to social, cultural, and economic characteristics as well as governmental policies. Changes in the profiles of people in different settings are important for policy makers and care providers. Although details will differ, how change occurs across time is important to all, including lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 25 publications
5
36
0
Order By: Relevance
“…Based on the qualitative and quantitative findings, no adverse effects were noted such as an increase in medication use or distress in family caregivers. The quantitative results were congruent with the qualitative results and showed a trend toward improvement on all These results were based on a sample of older people who had characteristics similar (severity of cognitive impairment, age) to the ones found in LTCF of various countries (Cohen-Mansfield & Werner, 1997;Matthews et al, 2016;Røen et al, 2017), except for gender. In these studies, 64 to 81% of participants were women.…”
Section: Discussionsupporting
confidence: 74%
“…Based on the qualitative and quantitative findings, no adverse effects were noted such as an increase in medication use or distress in family caregivers. The quantitative results were congruent with the qualitative results and showed a trend toward improvement on all These results were based on a sample of older people who had characteristics similar (severity of cognitive impairment, age) to the ones found in LTCF of various countries (Cohen-Mansfield & Werner, 1997;Matthews et al, 2016;Røen et al, 2017), except for gender. In these studies, 64 to 81% of participants were women.…”
Section: Discussionsupporting
confidence: 74%
“…The past two decades have seen reductions in the overall numbers in care homes but higher prevalence of functional and cognitive impairments among residents. 30 Our findings showed that more years were spent with high dependency, and that older people with substantial dependencies are now more likely to live supported in the community. If dependency prevalence remains constant, we estimate that by 2025 there will be an additional 353 000 older people with substantial dependencies; they will have complex care needs that require sustained input from family carers or community health or social care teams to support independent living.…”
Section: Discussionmentioning
confidence: 58%
“…We are uncertain whether the results from tertiary health care settings or nursing homes can be generalized to primary health care settings, considering that the patients in primary care can differ in their health profiles and comorbidities. 11,12 To this end, we sought to conduct a systematic review with meta-analysis to pool the adverse outcomes of PIP reported in the literature, specifically focusing on older persons in primary care.…”
mentioning
confidence: 99%